Environmental and economic implications of stormwater management alternatives in rural development. (26th January 2021) - Peterson, Lisa A.; Awerbuch, Patricia M.; Spatari, Sabrina
Abstract: Floodplain restoration as a means of stormwater management (SWM) can benefit communities and the environment but is uncommonly chosen due to limited familiarity in rural and urban planning. This study uses life cycle assessment and life cycle costing (LCC) to compare four SWM alternatives for a typical rural setting undergoing development. We evaluate a case study in Lancaster County, PA in the Chesapeake Bay Watershed which, through community stakeholder planning, undertook a novel SWM plan by restoring its historic floodplain. We evaluate the life cycle impact assessment (LCIA) metrics, global warming (GW), eutrophication and acidification and cost for each alternative over a 100‐year period of analysis including construction, maintenance, and end‐of‐life decommissioning. Assuming a 5% discount rate, and that soils do not require off‐site hauling due to contamination, the cost and LCIA metrics for floodplain restoration are not significantly higher than the more conventional surface basin alternative. Although LCC is highly sensitive to the transport of soil off‐site, more than doubling the costs for the underground stormwater infiltration basin (USIB) and increasing eightfold the cost for the floodplain restoration, contaminated soil removal is rarely needed on rural land. For USIB, LCIA metrics are sensitive to the choice of recycling versus incinerating plastic components, with recycling resulting in lower GW; and for the permeable pavement alternative, additional maintenance to extend its lifetime shows favorable cost and reduced GW. We conclude that in rural settings where soil is not contaminated, floodplain restoration offers environmental and social benefits for SWM that outweigh its costs.